Ethnic Identity and State Dysfunctionality in Post-Colonial African Societies: A Focus on Nigeria - BEREBON, Charles; UKULOR, Donatus (dialektika kontemporer, 2024)
The role of ethnicity in driving intergroup conflicts has sparked considerable debate. Many argue that ethnic tensions in Africa stem from historical colonialism, competition for political power and resources, and the absence of a unified national identity or shared values. This article explores the connection between colonization and ethnic crises in Africa, with a particular focus on Nigeria. It examines how ‘ethno-social identity’ is conceptualized and investigates the links between ethnic polarization, ‘ethnocorruption,’ insecurity, and separatism. The study highlights the dysfunctionality of the state and the identity challenges posed by ethnocentric federalism, particularly in relation to questions of personal identity within the population. Issues such as the ‘indigene versus non-indigene’ divide and the conflicting ethnic identities—such as ‘I am Hausa,’ ‘I am Fulani,’ ‘I am Yoruba,’ or ‘I am Igbo’—reflect the broader crisis. A minority of politically influential ‘tribeless elites’ continue to dominate the political landscape. In recent years, Nigeria has become increasingly plagued by ‘kidnapped democracy,’ insecurity, and corruption. Escalating conflicts, including clashes between Fulani herders and non-Fulani farmers, banditry, kidnappings for ransom, and the activities of ‘Unknown Gunmen,’ are further undermining national unity. Meanwhile, socio-economic stagnation and the erosion of moral values have driven many young Nigerians to either join movements like the Obidient group or seek opportunities abroad through the ‘Japa’ phenomenon